STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN PROFESIONAL GURU PADA SMA NEGERI 1 INDRAPURI KABUPATEN ACEH BESAR - Nurhusna Razali; Cut Zahri Harun; Sakdiah Ibrahim (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2014)
Abstract: Teachers’ professionalism ability to create quality learning affects the successful of education. Guiding the teachers is one of the principal’s responsibilities. This research aimed to find out the principal’s strategies including programs, implementation, evaluation, supporting and inhibiting factors in improving teacher’ professionalism at State Senior High School 1 of Indrapuri. This research employed a descriptive method with quantitative approach. Techniques of data collection used were interview, observation, and study documentation. Subjects were principals, vice principal, teachers, supervisors, and school committee. Data were analyzed by reducing data, displaying, drawing conclusion, and data verification. The results showed that: 1) planning to improve teachers’ professionalism was implemented in discussion forum at the beginning of academic year and involves all school personnel. Teachers’ professionalism improvement programs planned were implementing team teaching, involving all teachers in school activities, managing student’s administration including facilities and infrastructure, conducting supervision, instilling discipline, and giving motivation and reward accordingly. 2) The programs were implemented by the team, which consisted of the principal, vice principal and senior teachers. The programs were implemented by dividing the tasks and setting the planning as a reference. 3) The evaluation was conducted at the end of semester and guided the teacher to understand the evaluation activities, showing instrument evaluation, and socializing the evaluation activities. 4) The supporting factors in improving teachers’ professionalism were having a formal legal basis, the socialization regarding the importance of teachers’ professionalism, cooperation, partnership and potential teachers, and the existence of formal and informal organization in school. The inhibiting factors were the low of bureaucratic culture, the low of work productivity, the low of output education to compete, and incomplete of facilities and infrastructure.Keywords: Strategy, school principal, teacher’s professional.Abstrak: Strategi kepala sekolah merupakan cara untuk mengatasi segala kendala atau tantangan dengan memanfaatkan segala sumber daya sekolah, termasuk meningkatkan professional guru untuk mencapai tujuan pendidikan. Tujuan Penelitian ini untuk mengetahui strategi kepala sekolah dalam meningkatkan profesional guru. Penelitian ini menggunakan metode deskriptif dengan pendekatan kuantitatif. Teknik pengumpulan data adalah wawancara, observasi, dan studi dokumentasi. Subjek penelitian adalah kepala sekolah, wakil kepala sekolah, pengawas dan guru. Penyusunan rencana peningkatan profesional guru dilakukan dalam suatu forum musyawarah pada setiap awal tahun ajaran dengan melibatkan semua personel sekolah. Program peningkatan profesional guru yang direncanakan adalah melaksanakan team teaching, melibatkan seluruh guru dalam aktivitas sekolah, mengelola administrasi siswa, sarana dan prasarana, melakukan supervisi, menanamkan disiplin, memberikan motivasi dan penghargaan yang sesuai. 2) Pelaksanaan program dilakukan oleh tim yang terdiri dari kepala sekolah, wakil kepala sekolah dan guru senior. Pelaksanaan program diawali dengan pembagian tugas dan menjadikan perencanaan sebagai pedoman pelaksanaan. 3) Evaluasi dilaksanakan pada setiap akhir semester dengan terlebih dahulu membina guru untuk memahami kegiatan evaluasi, menunjukkan instrumen evaluasi dan mensosialisasikan kegiatan evaluasi. 4) Faktor pendukung dalam meningkatkan profesional guru adalah memiliki landasan yuridis formal, telah adanya sosialisasi tentang pentingnya profesional guru, adanya budaya gotong royong dan kemitraan dan potensi guru, dan adanya organisasi formal dan informal sekolah. Sedangkan hambatan adalah kultur birokrasi yang kurang baik, produktivitas kerja masih rendah, output pendidikan kurang mampu bersaing, sarana dan prasarana masih kurang.Kata kunci: Strategi Kepala Sekolah, Profesional Guru.